Optimisation of excitation tolerances for robust beamforming in linear arrays. Issue 2 (1st January 2016) - Anselmi, Nicola; Rocca, Paolo; Salucci, Marco; Massa, Andrea
Abstract : A method for robust amplitude beamforming in linear antenna arrays is presented. The admissible tolerances on the array excitations, described as real‐valued intervals, are maximised regardless their nominal values, while guaranteeing that the bounds of the radiated power patterns fit a‐priori defined mask constraints. A set of representative numerical results, concerned with different mask constraints as well as comparisons with state‐of‐the‐art approaches, is reported and discussed to assess the effectiveness of the proposed approach.